STRATEGI PEMBELAJARAN EACH ONE TEACH ONE DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Hariyanto Hariyanto; Arfandi Arfandi (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2023)
The results of observations at SMP Negeri 3 Situbondo showed that student learning outcomes in PAIBP material, especially the Thaharah subject, still reached the percentage of 50% or 16 students who completed out of 32 students. This is because students are still not able to master how to stay well. The reason is not only students but teachers who are less innovative in using learning strategies. Less varied learning models that have been applied by teachers in the field of study do not provide the widest opportunity for students to be active. Although the teacher has tried to make improvements, student learning outcomes are still relatively low. Therefore, efforts or methods can be made to improve student learning outcomes, one of which is by applying the each one teach one learning strategy. The each one teach one learning strategy, the reasons for using this strategy are 1) Support and improve the learning process. 2) Train students to be responsible. 3) This strategy can be used in all subjects: this research has two formulations (1) How is the implementation of the each one teach one learning strategy for the subject of PAIBP thaharah class VII material at SMP Negeri 3 Situbondo for the academic year 2021-2022?, (2) How is it improving student learning outcomes in PAIBP subjects through the implementation of the each one teach one learning strategy for class VII material at SMP Negeri 3 Situbondo for the academic year 2021-2022?. This study uses classroom action research with various kinds of data collection, namely observation, interviews and documentation. Based on the results of the research and discussion, it can be concluded as follows: (1) The application of the learning strategy of each one teach one subject of PAIBP thaharah class VII material at SMP Negeri 3 Situbondo in the 2021-2022 academic year is very effective, (2) There is an increase in student learning outcomes by 19% from 75% of the first cycle to 94% of the second cycle of PAIBP subjects through the application of the each one teach one learning strategy for class VII material at SMP Negeri 3 Situbondo in the 2021-2022 academic year.